Teaching evidence-based practice: perspectives of university nurse managers - Camargo, Fernanda Carolina (2021)
This study aims to understand the teaching of evidence-based practice from the perspective of university nurse managers. It is a study by mixed methods, according to the conception of Evidence-Based Practice, and by the Theory of Diffusion of Innovations, conducted by semi-structured individual interviews, using a hermeneutic-dialectic approach with the intentional sample of 10 nurse managers from a public university. The teaching of evidence-based practice took place through specific initiatives by teachers, during internships to raise a clinical question and search for evidence to answer it, or in search and critical analysis of scientific articles. The results support the orientation of the educational matrix in the training of nurses and indicate that contextual aspects influencing the adoption of evidence-based practice in teaching were recognized, recommending to increase both teaching and the production of knowledge on the subject.